Інформаційне забезпечення стратегічного управління підприємством в умовах глобалізації - Драган, Олена Іванівна; Бергер, Аліна Дмитрівна (My University, 2019)
У статті досліджується вплив інформаційного забезпечення на стратегію розвитку та управління розвитком підприємства. Розкриті сучасні завдання інформаційного забезпечення стратегічного управління підприємств м’ясопереробної галузі в умовах обмеження фінансово-інвестиційних ресурсів та глобалізації. Для розроблення стратегічного плану за всіма напрямками потрібно зібрати різносторонню інформацію для кожного рівня управління: стратегічного, тактичного, оперативного та запланувати виконання заходів на кожний рік відповідно до інформаційної піраміди. Запропоновано алгоритм пошуку інформації для підприємства м’ясопереробної галузі. The communication of strategic management of the enterprise of meat processing industry is investigated in the article. Influence of communication on development strategy and management of the enterprise is presented. Modern tasks of communication of strategic management of the enterprises of meat processing industry in the conditions of financially-investment resources limitation and globalization are exposed. For development of strategic plan after all directions, it is needed to collect different information for every level of management: strategic, tactical and operative and to plan implementation of events on every year in accordance with the informative pyramid. It is proved, that information about the environment of the enterprises of meat processing industry has non-system character. There is not enough clear information about the state and development of stock-raising, that testifies that enterprises work in the conditions of confinement conditions of raw materials resources. There is not enough information about scientific and technical achievements, branch innovations, consumers’ favour, import of meat products, raw material, spices, shells, prognoses of development of country’s economy that complicates the acceptance of strategic administrative decisions. The algorithm of information retrieval for the enterprise of meat processing industry is offered. Modern tasks of the existent associations of meat processors and producers of meat products of Ukraine must be oriented on defence and help to the enterprises, and also to assist the improvement of their communication in relation to different situations with the aim of increasing the market competitiveness. Web sites of well-known enterprises-leaders of meat processing industry are the company "Globino", Public Corporation “Yatran”, PJSC "Koziatynskyi meat processing plant", PJSC "Kremenchukmiaso", PJSC "APK0Invest” and others were educed some general characteristics of information marked on them were investigated. At the same time, much attention was paid to information that improved the image of meat processing plants due to placing on web sites.
Keywords: стратегічне управління; інформація; інформаційне забезпечення; розвиток; глобалізація; м’ясопереробна галузь; кафедра економіки праці та менеджменту; strategic management; information; communication; development; globalization of meat processing industry; кафедра маркетингу